HLA typing by next‐generation sequencing – getting closer to reality. Issue 2 (February 2014) - Gabriel, C.; Fürst, D.; Faé, I.; Wenda, S.; Zollikofer, C.; Mytilineos, J.; Fischer, G. F.
Abstract Next generation sequencing (NGS) denotes novel sequencing technologies that enable the generation of a large number of clonal sequences in a single sequencing run. NGS was initially introduced for whole genome sequencing and for quantitation of viral variants or genetic mutations in tumor tissues; more recently, the potential for high resolution HLA typing and high throughput analyses has been explored. It became clear that the complexity of the HLA system implicates new challenges, especially for bioinformatics. From an economical point of view, NGS is becoming increasingly attractive for HLA typing laboratories currently relying on Sanger based sequencing. Realizing the full potential of NGS will require the development of specifically adapted typing strategies and software algorithms. In the present review, three laboratories that were among the first to perform HLA‐typing using different NGS platforms, the Roche 454, the Illumina Miseq and the Ion Torrent system, respectively, give an overview of these applications and point out advantages and limitations.